Convivência com o Semiárido: a percepção do uso das tecnologias sociais hídricas em Ouro Branco-AL - Rodrigues, Allan Junior Silva (Universidade Federal Rural do Semi-Árido, 2021)
In the semi-arid region of Brazil, public policies for coping with drought have assumed significant relevance from the perspective of knowledge appropriation and application of technologies adapted to the local context. Among the possibilities, Social Water Technologies (STs) are essential, especially in rural areas with water scarcity due to the natural cycle of droughts. The One Million Cisterns Program - P1MC has been a successful experience. Specifically in the semi-arid region of Alagoas, the municipality of Ouro Branco stands out, where the program was implemented, as well as other strategies for living with water scarcity. Thus, the general objective of this research is to analyze the main contributions and socio-environmental impacts of the SRHs for coping with drought in the rural area of the municipality of Ouro Branco-AL. The procedures for the collection of information were developed in four stages: documental, bibliographical and photographic survey; diagnosis, by means of visits for the recognition of the HRTs existing in the communities; visits to the Municipal Secretary of Agriculture to obtain information about the localities subsequently mapped; application of questionnaires with the population and; realization of semi-structured interviews to help in the understanding of the use of the HRTs. We verified the possibilities of actions that, if properly prioritized, can significantly mitigate the socio-environmental impacts associated with drought, a historically recurring natural phenomenon in the semi-arid region. The actions related to the conditions imposed by nature should be formulated in the sense of coexistence, with technological strategies built on the basis of knowledge generated locally and collectively. Some HRTs were presented: weir, underground dam, clay pit, trench pit, popular water pump, cacimba, automatic detour, artesian well, stone tank, and cisterns. The governmental programs P1MC and P1+2 were considered important for rural families in the semi-arid region, regarding access to drinking water. In the municipality of Ouro Branco-AL, the HRTs verified are cisterns, weirs, artesian wells, and dams. However, the still persistent use of carro pipa and the little development of local agriculture and livestock are socio-environmental indicators that there is still much to do to achieve local water security
Keywords: P1MC; Cisternas; Seca no semiárido; Aspectos socioambientais; P1MC; Cisterns; Drought in the semiarid; Socio-environmental aspects; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES